Selfregulated learning: A key learning effect of feedback in a problembased learning context - A Louw; A Mubuuke; S van Schalkwyk (South African Medical Association, 2017)
Background. Problem-based learning (PBL) has been adopted across many health professions training institutions. Small-group student tutorials are a major component of PBL. Facilitator feedback during a tutorial is a key activity to promote self-regulated learning.Objective. To explore ways in which students use feedback to promote self-regulated learning in a PBL environment.Methods. This was an exploratory qualitative study in which individual interviews and focus group discussions were conducted with health science students who had experience of the tutorial process. Data were collected through audio recording and writing of field notes. Thematic analysis was employed to generate the reported themes.Results. Students used feedback in various ways that can lead to self-regulated learning. Their experiences were summarised into three themes, i.e. activation of prior knowledge; reflection; and formulation of a personal learning plan. From the findings, a conceptual model linking feedback and selfregulated learning in a PBL context was developed.Conclusion. In this study, we propose a conceptual model illustrating how feedback is a major activity in the critical pathway that leads to self-regulatedlearning.